Fog Computing Model for Evolving Smart Transportation Applications - Muzakkir Hussain, M.; Alam, Mohammad Saad; Sufyan Beg, M.M. (Fog and Edge Computing, 2019)
This chapter introduces the needs and prospects of adopting data‐drive transportation architectures and the landscape of smart applications supported over adoption of such data‐driven mobility models. It discusses which computer requirements can be best fulfilled through cloud computing and which require fog rollout. The chapter identifies the fog computing requirements of intelligent transportation systems (ITS) such as mission‐critical architectures. It assesses the state of cloud platforms to store and compute support for such applications and discusses the proper mix of both computational models to best meet the mission‐critical computing needs of smart transportation applications. The chapter presents a fog computing framework customized to support latency sensitive ITS applications. The fog orchestrating requirements in ITS domain are substantiated through an intelligent traffic lights management (ITLM) system case study. The chapter outlines the key big data issues, challenges, and future research opportunities, while developing a viable fog orchestrator for smart transportation applications.